Analysis of the Perception of Islamic Boarding School Residents Towards Halal Labeled Food (Case Study: PPAI Mambaunnur Islamic Boarding School) - Basuki, Hari; Abrohim , Maulana Bani (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2024)
In our daily lives as humans we cannot escape from consumer behavior. Factors that greatly influence consumer decisions to buy certain goods are definitely perceptions. Perception, according to the Big Indonesian Dictionary (KBBI), is the absorption and process of knowing several things through a person's five senses; direct response (reception) of something. The perception of residents of the PPAI Mambaunnur Islamic boarding school towards halal-labeled food products is that most of the residents of the Islamic boarding school agree with the halal label on a food product, the Islamic boarding school is a dormitory for studying the Koran. The approach used in this study is a qualitative approach based on problems that are intended to find each person's perception in responding to something according to their respective theories and understandings, not to seek generalizations. The data collection for this study uses observation, interview and documentation techniques. The data analysis techniques used are reduction, analysis and then drawing conclusions. The results of the study showed that out of 22 informants, 16 informants/people agreed and 6 others did not agree and this is a natural thing because each has different knowledge and understanding and the residents of the Islamic boarding school themselves already know the rules or understanding of halal and thoyib food well according to their respective understandings or understandings. and from the residents of the PPAI Mambaunnur Islamic boarding school, it can be said that they all know the halal label from several media or other methods such as knowing from the packaging or other information such as the internet or other social media.